Evaluating the "satisfaction" and "self-confidence" in nursing students in undergoing simulated clinical experiences - Cristiane Chaves de Souza; Willians Guilherme dos Santos; Patrícia de Oliveira Salgado; Pedro Paulo do Prado Junior; Luana Vieira Toledo; Luciano Côrtes Paiva (SciELO, 2020)
Abstract Objective: To evaluate the "satisfaction" and "self-confidence" constructs in nursing students who underwent simulated clinical experiences in semiology and semiotechnique disciplines. Method: A descriptive study developed with Nursing students from a federal public university in the interior of Minas Gerais through weekly simulated workshops. The "satisfaction" and "self-confidence" constructs were evaluated by the "Student Satisfaction and Self-Confidence with Learning Scale" and "Simulated Clinical Experiences Satisfaction Scale". Results: The final sample was 45 students. Most were more satisfied (overall average = 4.18) than self-confident (overall average = 4.12). The Spearman correlation test identified a significant and positive association between the "satisfaction" and "self-confidence" constructs. Conclusion: Students feel self-confident and satisfied with the use of simulation as an active teaching-learning methodology, highlighting that the higher the satisfaction level, the greater the student's self-confidence.